Recommendations for gonadotoxicity surveillance in male childhood, adolescent, and young adult cancer survivors: a report from the International Late Effects of Childhood Cancer Guideline Harmonization Group in collaboration with the PanCareSurFup Consortium. Issue 2 (February 2017) - Skinner, Roderick; Mulder, Renee L; Kremer, Leontien C; Hudson, Melissa M; Constine, Louis S; Bardi, Edit; Boekhout, Annelies; Borgmann-Staudt, Anja; Brown, Morven C; Cohn, Richard; Dirksen, Uta; Giwercman, Alexsander; et al.
Summary: Treatment with chemotherapy, radiotherapy, or surgery that involves reproductive organs can cause impaired spermatogenesis, testosterone deficiency, and physical sexual dysfunction in male pubertal, adolescent, and young adult cancer survivors. Guidelines for surveillance and management of potential adverse effects could improve cancer survivors' health and quality of life. Surveillance recommendations vary considerably, causing uncertainty about optimum screening practices. This clinical practice guideline recommended by the International Late Effects of Childhood Cancer Guideline Harmonization Group in collaboration with the PanCareSurFup Consortium, developed using evidence-based methodology, critically synthesises surveillance recommendations for gonadotoxicity in male childhood, adolescent, and young adult (CAYA) cancer survivors. The recommendations were developed by an international multidisciplinarypanel including 25 experts in relevant medical specialties, using a consistent and transparent process. Recommendations were graded according to the strength of underlying evidence and potential benefit gained by early detection and appropriate management. The aim of the recommendations is to enhance evidence-based care for male CAYA cancer survivors. The guidelines reveal the paucity of high-quality evidence, highlighting the need for further targeted research.